2019
DOI: 10.3390/ani9080488
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and Contrasting Knowledge on Mules and Hinnies as a Tool to Comprehend Their Behavior and Improve Their Welfare

Abstract: Mules and hinnies are the hybrids between donkeys (Equus asinus) and horses (Equus caballus). For centuries, mankind has used them for agrarian purposes, the military, or recreation. Contrasting literature with behavioral observations, we seek a better behavioral understanding andthus comprehensive solutions for their welfare enhancement. Over the past 6 years, we have assessed physical and behavioral welfare in over 900 mules by surveying owners from Egypt, Peru, Portugal, Spain, Mexico, and the U.S. These mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
0
18
0
8
Order By: Relevance
“…Hybrids showed the higher number of reactions perceived as more averse. In a study focused on hybrids' behaviour, McLean et al 28 identified that mule owners and handlers find it easier to interact with their animal when compared to allowing a stranger to do so. Therefore, it is possible that the presence of the assessors, assumed as strangers by the mules, explain the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrids showed the higher number of reactions perceived as more averse. In a study focused on hybrids' behaviour, McLean et al 28 identified that mule owners and handlers find it easier to interact with their animal when compared to allowing a stranger to do so. Therefore, it is possible that the presence of the assessors, assumed as strangers by the mules, explain the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Mules are the least studied equids [ 38 ], but they have gained increasing attention in the scientific literature in the last decade in terms of their physiology and behavior. The aim of adding knowledge about the mule-human interaction is that the present study analyzed attitudes and perceptions of a group of soldiers towards mules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the colonial times in America, the hierarchy between the Spanish elite, Mulato laborers and the indigenous workforce was rendered as an analogy of the hierarchy between horses, mules and donkeys [ 51 ]. In the same line, recent studies show that handlers frequently describe mules as difficult to handle and aggressive [ 18 , 38 , 40 ]. Contrary, in the present study, a negative bias was found for donkeys, and horses were only perceived as more expensive and less aggressive than mules.…”
Section: Discussionmentioning
confidence: 99%
“…Mules are prized for their strength which is harnessed in agriculture and are preferred over and above horses and donkeys for this ‘heavy work’ such as ploughing, despite their reputation of being temperamentally harder to work with. Negative reactions are particularly seen in response to unfamiliar individuals and have been associated with handling methods 26,27 . Mules are increasing in value as they are becoming more rare and the ability to hire them for agriculture has been highlighted as an important source of income for many owners in Mexico 10 .…”
Section: Discussionmentioning
confidence: 99%